2013
DOI: 10.1044/0161-1461(2012/11-0055)
|View full text |Cite
|
Sign up to set email alerts
|

Readability of Questionnaires Assessing Listening Difficulties Associated With (Central) Auditory Processing Disorders

Abstract: In an effort to decrease respondent burden, developers should consider readability as another testable psychometric construct. Clinicians should take into account the functional health literacy skills of adult proxy respondents when giving self-administered questionnaires.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 52 publications
5
25
0
Order By: Relevance
“…In contrast, the CPSI and the IIEF, including its short form, have a readability level that has to be considered as clearly too difficult according to all tests that were applied. These findings are largely consistent with assessments of questionnaires in other medical fields [56711]. …”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In contrast, the CPSI and the IIEF, including its short form, have a readability level that has to be considered as clearly too difficult according to all tests that were applied. These findings are largely consistent with assessments of questionnaires in other medical fields [56711]. …”
Section: Discussionsupporting
confidence: 85%
“…Like similar studies in different fields of medicine [67], they reported on generally satisfactory results. However, all of these studies evaluated the average readability of the complete questionnaires.…”
Section: Introductionsupporting
confidence: 61%
“…Audiologists may incorporate values central to patient-centred care (such as patient engagement, patient narrative, and mutual understanding) into their clinical practice through the use of patient-reported outcome measures (PROMs). Previous research suggests that the readability of many patient-reported outcome measures available for use within the field of adult audiologic rehabilitation exceed the 4 th to 6 th grade reading level recommended by health literacy experts (Atcherson, Richburg, Zraick, & George, 2013;Atcherson, Zraick, & Brasseux, 2011;Kelly-Campbell, Atcherson, Zimmerman, & Zraick, 2012).…”
Section: Overviewmentioning
confidence: 99%
“…Since the 1920s, educators have been using vocabulary and sentence length as a way to predict the apparent difficulty, or readability, of a text (Atcherson et al, 2013;DuBay, 2004). This method has been firmly entrenched with the use of readability formulas, a practice which can boast more than eighty years of application (DuBay, 2004).…”
Section: Readability Formulasmentioning
confidence: 99%
“…As a result, readability formulas continue to be used as the sole judgment tool to assess text in a variety of settings and topics. For example, they are used to evaluate surveys [19], patient information leaflets provided by hospitals [20], or website discussing a variety of topics such as ear tubes [21], speech and language difficulties [22], and nephrology articles on Wikipedia [23] among others.…”
Section: Text Readabilitymentioning
confidence: 99%